Math, asked by teju7326, 1 year ago

fast fast fast paper hai

Attachments:

Answers

Answered by gouri4199
1

Answer:

 \: by \: remaindertheoram \\  \: x + 1 = 0 \\ x = 0 - 1 \\ x =  - 1 \\p(x) = (x {}^{31}   + 31) \\ p( - 1) =  ( - 1) {}^{31 +}  + 31 \\  - 1 + 31 = 30 \\ so \: remainder \: can \: be \: 30

Hope you like

Answered by ayushmang4428
1

Answer:

BY USING REMAINDER THEOREM

is in the picture ... mark as brilliant

and follow me Instagram

ayushman_gupta_04

to talk to me ... good night

Attachments:
Similar questions